Life without limits : inspiration for a ridiculously good life - Vujicic, Nick (Colorado Springs, CO : Waterbrook Press, 2012)
Born without arms or legs, Vujicic overcame his disability to live not just independently but a rich, fulfilling life, becoming a model for anyone seeking true happiness. Now an internationally successful motivational speaker, his central message is finding life's purpose.
If you can't get a miracle, become one -- No arms, no legs, no limits -- Full assurance in the heart -- Love the perfectly imperfect you -- Attitude is altitude -- Armless but not harmless -- Don't let your face plant grow roots -- The new bloke in the bushes -- Trust others, more or less -- An equal opportunity hugger -- The ridiculous rules -- Make giving your mission.
Includes'Bonus: Personal Action Plan' page [231] - 264.
Keywords: Vujicic, Nick; Christian life; Happiness -- Religious aspects -- Christianity